THE ROLE OF CORPORATE GOVERNANCE IN ADVANCING SOCIAL SUSTAINABILITY: A COMPARATIVE STUDY ACROSS MANUFACTURING INDUSTRIES - Shaifali (International Journal of Research -GRANTHAALAYAH, 2025)
This research explores corporate governance's role in ensuring social sustainability throughout manufacturing sectors by qualitative, comparative means. The study applies thematic analysis to responses from semi-structured interviews with textile, automobile, and electronics sector governance and sustainability experts to reveal how governance shapes socially responsible behavior. The research identifies four governance mechanisms central to social sustainability—ethical leadership and board make-up, stakeholder interaction, human capital improvement, and strategic alignment of social goals—that work together to promote social sustainability. Of particular interest, industry-specific variations of governance practices mirror unique operating issues and regulatory requirements. This work contributes to the emerging ESG conversation by emphasizing governance as an affirmative facilitator of social sustainability as opposed to a compliance function. The research emphasizes the importance of incorporating social values into governance frameworks by way of participatory decision-making, transparency, and accountability. The findings provide policy advice to policymakers as well as corporate leaders who seek to engender inclusive and equitable development through governance reforms.